Pengembangan Instrumen Perilaku Mencari Bantuan pada Generasi Z di Suku Madura - Indriyawati Indriyawati; Ahmad Guntur Alfianto; Mn. Lisan Sediawan (Puslitbang Sinergis Asa Professional, 2022)
Help seeking behavior is an activity carried out by someone consciously to get help regarding the problem at hand. Help seeking behavior is part of a form of problem-solving strategy or coping strategy. Not a few people, especially Generation Z, have not received assistance properly and correctly in dealing with their problems because it is caused by several factors. Generation Z or the so-called net generation is a generation that tends to be active, meaning that this generation is easy to learn and practice something they want to learn. The General Help Seeking Questionnaire (GHSQ) is a questionnaire used to measure a person's behavior in help seeking. The purpose of this study was to test the validity and reliability of the GHSQ with the aim that the questionnaire could be used by Generation Z and the Madurese community in measuring a person's intention to seek help. This study uses an analytical survey method with a cross sectional approach on 100 samples of Generation Z in the Madura Tribe. The results of the validity test for 100 samples of Generation Z in the Madurese showed that the GHSQ questionnaire consisting of 10 question items was declared valid with a calculated r value of <0.2072 and the reliability test results obtained a Cronbach's Alpha value of 0.840. So based on these results it can be concluded that the GHSQ questionnaire is valid and reliable to be used in measuring the behavior of seeking help in generation Z in the Madurese.